12 Characterising remote memory in posterior cortical atrophy. Issue 8 (13th July 2017) - Ahmed, Samrah; Irish, Muireann; Loane, Clare; Baker, Ian; Husain, Masud; Thompson, Sian; Blanco, Cristina; Mackay, Clare; Zamboni, Giovanna; Foxe, David; Hodges, John R; Piguet, Olivier; et al.
Abstract : Objective: Posterior cortical atrophy (PCA) is a syndrome characterised by progressive disruption of visual processing and neurodegeneration in the parieto-occipital cortex. The most common underlying cause is Alzheimer's pathology. Anterograde memory function and the medial temporal lobes (MTLs) are thought to be relatively preserved. Given that the typical pattern of atrophy in PCA overlaps with brain networks critical for the recollection of personal events, we hypothesised that patients would be impaired on a test of autobiographical memory. Method: 14 PCA, 18 Alzheimer's disease (AD) patients and 28 healthy controls completed the Autobiographical Interview. Results: Both PCA and AD patients produced significantly less internal detail relevant to the chosen memories, compared with controls. However, the PCA group also produced a significantly greater amount of unrelated external detail compared with controls and AD. Across the lifespan, PCA and AD again showed similarly poor recall of relevant remote memory details compared with controls, with no temporal gradient evident in either group. Correlational analysis in PCA patients revealed a significant relationship between total external details and the Hayling test of inhibitory control, and a trend towards significance between internal details and visual imagery. Conclusion: Our findings suggest that, despite relatively preserved MTL structures, PCA patients have significantly impaired remote memory. We propose that damage to posterior regions of the brain disrupts access to visual information integral to the autobiographical memory trace. Increased provision of external details may be a compensatory strategy due to lack of access to details relevant to episodic memories.